Dietary intake polycyclic aromatic hydrocarbons (PAHs) and associated cancer risk in a cohort of Chinese urban adults: Inter- and intra-individual variability. (February 2016) - Duan, Xiaoli; Shen, Guofeng; Yang, Hongbiao; Tian, Jing; Wei, Fusheng; Gong, Jicheng; Zhang, Junfeng(Jim)
Abstract: Dietary intake is one of the major exposure pathways of polycyclic aromatic hydrocarbons (PAHs), especially in Chinese people because foods are often prepared with grilling and/or frying that would produce high levels of PAHs. In this paper, we assessed daily dietary intakes (DDI) of PAHs, using a "duplicate plate method", among 100 Chinese urban residents. The DDI of benzo(a)pyrene ranged from 0.06 µg per day to 13.5 µg per day with a median of 0.69 µg per day, varying largely across subjects. The median Incremental Lifetime Cancer Risk (ILCR) attributable to PAH dietary intake was 6.65 × 10 −5 (4.41 × 10 −5 to 1.02 × 10 −4 as inter-quartile range). The contribution of several high-PAH containing foods like barbecued, smoked or deep-fried meats to the overall DDIs was about 13%. The use of raw foods may underestimate dietary intake of PAHs and associated exposure risk considerably. Results from foods sampled in different seasons suggested that seasonal variability within an individual may contribute notably to overall variability measured in a population and more future studies with longer-term investigation on food ingestion and pollutant exposure are needed. The study indicates that measuring actually consumed foods is more appropriate for dietary intake exposure assessment, and intra-individual variance should be taken into account during study design and data analysis. Highlights: Duplicated plate method to estimate dietary intake exposure of priority PAHs. Serious ingestion exposure risk associated with cooked food intake among Chinese residents. Use of raw foods underestimates dietary intake dose and consequent exposure risk. Within-subject variation contributes notably to the overall variation in dietary intake. Risk due to dietary PAH intake is comparable to that from the inhalation exposure.